Necrotizing Pancreatitis in a Patient Diagnosed With SLE: A Rare Case Report - Maryam Javid; Tohid Damideh; Omid Pourbagherian; Mehdi Jafarpour (Clinical Case Reports)
ABSTRACT Necrotizing pancreatitis is an extremely rare but serious complication of systemic lupus erythematosus (SLE). Early recognition and appropriate treatment, including steroids and immunosuppressive therapy, are critical for improving outcomes in SLE patients with this condition.